THE EFFECTIVENESS OF THE USE OF DIGITAL TEXBOOKS ON THE EVALUATION OF BIOLOGY LEARNING COURSE ON PORTFOLIO ASSESSMENT MATERIALS - Hasruddin Hasruddin; Aryeni Aryeni; Widya Arwita (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2022)
Portfolio-based research is an important and inseparable part of the various skills that prospective biology teacher students need to possess. This development research using the ADDIE Model involved 92 students as research subjects, and 3 lecturers who were in charge of the Biology Learning Evaluation course. Subjects were determined by purposive sampling technique. Data related to the readiness of portfolio development in digital textbooks were used in questionnaires, and data related to portfolio-based assessment abilities were used, and were complemented by in-depth interviews with the lecture team of lecturers. Furthermore, the data were analyzed using the percentage technique to see the tendency of the respondent's condition. The results of the study found that 87.76% of respondents said that the portfolio material in textbooks was effective to be taught to prospective biology teacher students or in the very good category. The results of the evaluation of the portfolio-based assessment ability are included in the very good category as much as 72.41% and in the good category as much as 27.59%.